Development of Earth/Climate System Models in China： A Review from the Coupled Model Intercomparison Project Perspective - 周天军 邹立维 吴波 金晨曦 宋丰飞 陈晓龙 张丽霞 (Acta meteorologica Sinica, 2014)
The development of coupled earth/climate system models in China over the past 20 years is reviewed, including a comparison with other international models that participated in the Coupled Model Intercom- parison Project （CMIP） from phase 1 （CMIP1） to phase 4 （CMIP4）. The Chinese contribution to CMIP is summarized, and the major achievements from CMIP1 to CMIP3 are listed as a reference for assessing the strengths and weaknesses of Chinese models. After a description of CMIP5 experiments, the five Chinese models that participated in CMIP5 are then introduced. Furthermore, following a review of the current status of international model development, both the challenges and opportunities for the Chinese climate modeling community are discussed. The development of high-resolution climate models, earth system mod- els, and improvements in atmospheric and oceanic general circulation models, which are core components of earth/climate system models, are highlighted. To guarantee the sustainable development of climate system models in China, the need for national-level coordination is discussed, along with a list of the main compo- nents and supporting elements identified by the US National Strategy for Advancing Climate Modeling.